2015
DOI: 10.14243/jsaem.23.521
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristic Analysis and Experimental Verification of 2-DoF Resonant Actuator under Feedback Control

Abstract: The dynamic characteristics of a proposed two degree-of-freedom (DoF) actuator under amplitude feedback control are investigated in this paper. The feature of our proposed two DoF resonant actuator is that movement in the xand z-axes can be independently controlled by vector control. Two controllers: a PID controller and a proxy-based sliding mode (PSM) controller were compared for amplitude feedback control. A simulation model using finite element method (FEM) and MATLAB/Simlink is made, and the dynamic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In order to broaden the application range of LRAs, various kinds of multi-degree of freedom (DOF) resonant actuators have been developed [6,7]. Authors have also proposed a two degree-of-freedom resonant actuator that was able to be independently driven in x-and z-axes by vector control [8][9][10]. Additionally, authors have designed a three-DOF resonant actuator driven by conventional vector control [11].…”
Section: Introductionmentioning
confidence: 99%
“…In order to broaden the application range of LRAs, various kinds of multi-degree of freedom (DOF) resonant actuators have been developed [6,7]. Authors have also proposed a two degree-of-freedom resonant actuator that was able to be independently driven in x-and z-axes by vector control [8][9][10]. Additionally, authors have designed a three-DOF resonant actuator driven by conventional vector control [11].…”
Section: Introductionmentioning
confidence: 99%
“…To broaden the application range of LRAs, various kinds of multi-degree of freedom (DOF) resonant actuators have been developed (Suzuki et al, 2010;Yamaguchi et al, 2009). Authors have also proposed a two-DOF resonant actuators that was able to be independently driven in x-and z-axes by vector control (Yoshimoto et al, 2012(Yoshimoto et al, , 2014(Yoshimoto et al, , 2015, and the effectiveness of the actuator was confirmed through three-dimensional (3D) finite element analysis (FEA) and measurement on a prototype.…”
mentioning
confidence: 99%